Academic libraries and student learning outcomes. Issue 1 (5th February 2018) - Blummer, Barbara; Kenton, Jeffrey M.
Abstract : Purpose: The purpose of this paper is to examine the literature on student learning outcomes and academic libraries. An analysis of 81 papers revealed the following themes: outcomes assessment of library skills instruction, tools for assessing students' achievement of learning outcomes, institutional accreditation and student learning outcomes, academic libraries' impact on student learning outcomes, and the creation of learning outcomes. An understanding of these themes highlights how student learning outcomes are created, assessed, and valued in the academy. Design/methodology/approach: The methodology centered on a literature review of student learning outcomes and academic libraries from 2001 to the present. To identify relevant articles on this topic, the authors searched the library literature with various combinations of the following keywords: learning outcomes, library, academic, university, college, and higher education. Findings: An analysis of 81 papers on student learning outcomes and academic libraries revealed the following five themes: outcomes assessment of library skills instruction, assessment tools for student learning outcomes, institutional accreditation and student learning outcomes, academic libraries' impact on student learning outcomes, and the creation of learning outcomes. Research limitations/implications: The research was limited to articles published in English and after 2000. Practical implications: The findings can be utilized to inform instructional librarians about creating and assessing student learning outcomes. In addition, the paper can assist librarians in forging partnerships with academic departments and faculty in creating student learning outcomes to support course and departmental outcomes and accreditation efforts. Originality/value: The research offers librarians opportunities to incorporate student learning outcomes in library instruction as well as collaborate with faculty in creating student learning outcomes.